(untitled) (Indian Journal of Applied-Basic Medical Sciences, 2021)
Background: Parathyroid adenoma is a benign tumour of parathyroid gland and most common cause of primary hyperparathyroidism. Most common age group affected is 5-6th decade. Parathyroid adenoma causes elevated level of parathormone hormone and serum calcium. Method: A retrospective study was done in a case of 22 years old female having pathological fracture and on examination found to have neck mass and was diagnosed as parathyroid adenoma of left inferior gland with bone pathology. Patient undergone left inferior parathyroidectomy ,specimen was sent to histopathology department and HPE confirmed the diagnosis of parathyroid adenoma. Patient was followed up and did well after surgery. Observation: Parathyroid adenoma most commonly present as solitary gland enlargement and most common in the inferior parathyroid glands (75%) followed by superior parathyroid glands (15%) and anomalous position (10%). Of the latter 70% are in mediastinum and rest are in intra thyroid location. It is mainly sporadic and more common in female with male to female ratio being 1:3. Multi glandular adenomas are seen in familial syndromes and lithium induced PHPT.Conclusion:Parathyroid adenoma is a rare presentation in young adult. With correlation of clinical findings, biochemical and radiological investigation and histopathological examination parathyroid adenoma can be diagnosed easily.